Clinical trial analyzing the impact of continuous defocused CO2 laser vaporisation on the malignant transformation of erosive oral lichen planus. Issue 8 (October 2015) - Mücke, Thomas; Gentz, Irina; Kanatas, Anastasios; Ritschl, Lucas M.; Mitchell, David A.; Wolff, Klaus-Dietrich; Deppe, Herbert
Abstract: The erosive oral lichen planus (OLP) represents a management challenge to the clinician and can have debilitating consequences to patients' quality of life. The aims of this work were to determine the incidence of malignant transformation to squamous cell carcinoma (SCC) in patients undergoing traditional symptomatic treatments (oral salve containing lidocaine hydrochloride or systemic diclofenac) compared to patients that were managed with a defocused continuous CO2 laser beam. A total of 171 patients with histologically confirmed erosive OLP were included into this study. After treatment, patients were assessed until completion of wound healing, at least every 3–6 months for the first 2 years, and every 6–12 months thereafter. The study included 87 women (50.9%) and 84 men (49.1%). A total of 103 patients (60.2%) underwent symptomatic conservative treatment, and 68 patients (39.8%) underwent continuous defocused CO2 laser treatments. SCC developed in 16 patients (9.4%), 2 patients (2.9%) after continuous defocused CO2 laser treatment and 14 patients (13.6%) with symptomatic treatment only. This study provides insight into the potential impact of the CO2 laser in the management of patients with erosive OLP and the influence on the recurrence rate of erosive OLP, as well as malignant transformation to oral SCC.